Textism in English: Relationship between use of textese and reading comprehension competency among ESL undergraduates - Foong, Kok Hey (2021)
The trend of textism affecting language use in the past decade has led to past studies identifying the various implications of textism on reading comprehension competency among native users of English, but the problem lies in that the literacy skills of the tested participants are polished to a certain extent through exposure to the language since birth, both in its linguistic features, and cultural and educational background. With that, this paper sets out to investigate the behaviour in use of textism, extent of metalinguistic knowledge of textism, and effects of textism on reading comprehension competency among ESL undergraduates. To that end, this qualitative study recruits the use of a three-part measure, including a total of six tasks: semistructured interview, to test use of textism and use of first language; textism proficiency translation task and textism familiarity translation task, to test metalinguistic knowledge of textism; and nonword task, gap-filling task, and MUET reading model test, to test orthographic awareness, syntactic awareness, and reading literacy ability respectively. Evidently, our study findings echo those of past studies reviewed, showing no clear correlation between textism usage and reading comprehension competency. A gradual change in the digital sociolinguistic setting is also hinted by comparing present and studies from close to a decade ago. Nonetheless, this research study poses few limitations and research gaps, where the inclusion of predictive text and autocorrect is not factored in our framework. Besides, the demographic of the sampled participants could be improved upon, such as their first languages and their general age group.